FAKTOR-FAKTOR YANG MEMPENGARUHI MAHASISWI DALAM MEMILIH JURUSAN TEKNIK SIPIL DI UNIVERSITAS RIAU - Elva Manda Sari; Ashaluddin Jalil (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research is done at Riau's University that its research object is Civil Tech coed. To the effect of observational it it to know factor that regard coed in choose civil tech majors that per se its environment dominated by male.Population of this research is coed of generation 2004 until generation 2013 one get Civil Tech majorses at Universities Tech Faculty Riau. Sample of this research it generation coed 2011 until 2013 by use of sampling quota method by takes 30% of all told 3 generations. And sample amount of this research it 27 Civil Tech coeds at Riau's University.This research is done on year month of September 2014, this research is direct being done at civil tech environment. Of this research result factor what does dominate to regard coed in mamilih civil tech majors it because alone push.Keywords :Adaptation, Motivation, Coed In Chooses Majors